Analisis Pembelajaran Algoritma Pemrograman - Cindy Kawilda Hasibuan; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
Programming algorithm learning analysis is a study that examines the approaches, methods, and results of the algorithm teaching and learning process in the world of programming. This research looks at whether algorithms are only used in the computer world. The results of analysis or research show that learning algorithms are not only used in the computer world, but these algorithms can also be used in everyday life and even everything we do in the real world. Most of them are said to be related to algorithms. Therefore, this analysis highlights the importance of diverse approaches in teaching programming algorithms. Then the aim of writing this article is to analyze or find out how the programming algorithm learning process works, where with a deeper understanding of the programming algorithm learning process, it can be hoped that the quality of programming education and students' ability to understand and apply algorithm concepts in the programming world and the real world will improve. This research uses a descriptive method, where the author analyzes, summarizes and describes different situations and conditions from different sources so that they are collected into an article. Collecting data or information sources is carried out using library research techniques from journals, books and internet media which are used as reference material relating to the title discussed, namely learning analysis of programming algorithms with more accurate data and clear sources